The effect of social support on the self-efficacy of parents of children with autism through the mediation of emotional intelligence - Aini Shafra Anwar; Salamiah Sari Dewi; Suaidah Lubis (Institute of Computer Science (IOCS), 2026)
Parenting a child with Autism Spectrum Disorder (ASD) presents unique challenges that can lower parents' self-confidence and self-efficacy. While social support is considered a crucial external factor, its effectiveness in boosting self-confidence often depends on internal factors, such as emotional intelligence. The purpose of this study was to examine the mediating role of emotional intelligence in the relationship between social support and self-confidence in parents of children with autism. This study used a quantitative approach with a purposive sampling technique. Data were collected from respondents, parents of children with autism, using instruments such as the Multidimensional Scale of Perceived Social Support (MSPSS). Data analysis was performed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results of a study of 153 parents of autistic children showed that social support influenced self-confidence by 51.7% with a p value <0.001. Social support influenced emotional intelligence by 57.3% with a p value <0.001, and emotional intelligence influenced self-confidence by 36.5% with a p value <0.001. Thus, it can be concluded that increasing social support can increase the self-confidence of parents of autistic children through their emotional intelligence.